Hepcidin and iron-related gene expression in subjects with Dysmetabolic Hepatic Iron Overload - Barisani, Donatella; Pelucchi, Sara; Mariani, Raffaella; Galimberti, Stefania; Trombini, Paola; Fumagalli, Daniela; Meneveri, Raffaella; Nemeth, Elizabeta; Ganz, Tomas; Piperno, Alberto (Journal of hepatology, 2008)
Many patients with hepatic iron overload do not have identifiable mutations and often present with metabolic disorders and hepatic steatosis. Since the pathophysiology of Dysmetabolic Hepatic Iron Overload (DHIO) is still obscure, the aim of this study was to evaluate, in these patients, possible alterations in iron-related molecule expression. Iron-related gene mRNA levels were determined by quantitative-PCR in liver biopsies of subjects with NAFLD without iron overload and patients with HFE-hemochromatosis, β-thalassemia major and DHIO. Urinary hepcidin was measured by immunoblotting. No alterations in mRNA expression of either iron transporters or exporters were found in DHIO. mRNA and urinary hepcidin levels normalized for the amount of iron overload showed a significantly lower ratio than in controls, although not as low as in hemochromatosis or β-thalassemia. Differently from what observed in hemochromatosis, hepcidin mRNA did not correlate with urinary hepcidin. Patients with DHIO show appropriate regulation of mRNAs encoding proteins involved in iron uptake and efflux but dysregulation of hepcidin production. The relatively elevated urinary hepcidin can explain the iron phenotype in DHIO (more macrophage iron retention and low/normal transferrin saturation).